Spin-sensitive atom scattering via spin-orbit interaction - Zheng, Ren-Fei; Li, Zheng-Chun; Qin, Jie-Li; Zhang, Weiping; Zhou, Lu; Li, Yan (The European physical journal. D, Atomic, molecular, and optical physics, 2020)
We study the spin-sensitive scattering of the spin-orbit (SO) coupled cold atom subject to a moving spin-independent rectangular potential barrier. Due to that SO coupling breaks Galilean invariance, the spin orientation of the atom can be switched unidirectionally and thus can serve as a one-way spin switch. Different atomic scattering processes are analyzed at different barrier velocities. We explore the spin polarization rate and the transmission coefficient in a wide range of barrier velocities and find good agreement with the corresponding experiment. The spin switch can reach an efficiency close to 1 at appropriate parameters. This study presents a comprehensive understanding of the physical mechanism underlying the system’s function as a spintronic device. Graphical abstract